2018
DOI: 10.3389/fmicb.2018.01378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Antimicrobial Activities of Four Honeys From Three Countries (New Zealand, Cuba, and Kenya)

Abstract: Skin and chronic wound infections are an increasing and urgent health problem worldwide. Their management is difficult and the development of antibiotic resistance by both planktonic and biofilm-associated bacteria necessitates the use of alternative treatments. The purpose of this study was to compare the antimicrobial activity of four honeys from different floral and geographical origins: Melipona beecheii honey (Cuba) and three Apis mellifera honeys [Manuka honey (New Zealand), A. mellifera honey (Cuba), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 44 publications
3
30
0
1
Order By: Relevance
“…The results indicated that M . beecheii honey stood out because of its acidity and produced the best antimicrobial and antibiofilm activity against Staphylococcus aureus and Pseudomonas aeruginosa cells that was associated with induced structural changes observed by transmission electron microscopy, making it a possible candidate for wound infection treatment ( Morroni et al 2018 ).…”
Section: Parameters Related To the Antimicrobial Activity Of Honeymentioning
confidence: 99%
“…The results indicated that M . beecheii honey stood out because of its acidity and produced the best antimicrobial and antibiofilm activity against Staphylococcus aureus and Pseudomonas aeruginosa cells that was associated with induced structural changes observed by transmission electron microscopy, making it a possible candidate for wound infection treatment ( Morroni et al 2018 ).…”
Section: Parameters Related To the Antimicrobial Activity Of Honeymentioning
confidence: 99%
“…For millennia, the medicinal properties of honey have been used by mankind. This popular bee product is versatile and is effective against microbes [1][2][3][4], reducing inflammation [5], combating cancer [6], hypertension [7], and liver disease [8], aids in wound healing [3,9] and provides cough relief [10]. An important therapeutic quality of honey is its antimicrobial activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…ISSN Impreso: 0034-7744 ISSN electrónico: 2215-2075 se ha vuelto constante (Morroni et al, 2018). Estudios recientes han demostrado que los propóleos son una fuente de compuestos bioactivos con distintas actividades; antibacterial, fungistática, antiviral, antioxidante, antiinflamatoria, citotóxica y anticancerígena (Sartori et al, 2012, Popova, Chinou, Marekov, & Bankova, 2013, Choudhari, Haghniaz, Rajwade, & Paknikar, 2013, Inui et al, 2014, Nina et al, 2015.…”
unclassified